Darius the Great is not okay [large type] - Khorram, Adib (Thorndike Press, a part of Gale, a Cengage Company, 2019)
Clinically-depressed Darius Kellner, a high school sophomore, travels to Iran to meet his grandparents, but it is their next-door neighbor, Sohrab, who changes his life.